FRI0384 Primary sjÖgren's syndrome stratified based on the severity of patient-reported fatigue. (12th June 2018) - Gandolfo, S.; Doriguzzi Breatta, E.; Fabro, C.; Zandonella Callegher, S.; Quartuccio, L.; De Vita, S.
Abstract : Background: fatigue is one of the most common symptoms reported by patients affected by primary Sjögren's syndrome (pSS), and a major contributor to impaired quality of life. Objectives: to analyse the clinical, serological and histological features of pSS patients stratified according to the severity of their self-reported fatigue. Methods: among pSS patients undergoing clinical evaluation in our Sjögren's Clinic in a six-months period (January-June 2017), 86 consecutive unselected patients, fulfilling the latest ACR/EULAR pSS classification criteria, accepted to report their degree of fatigue on a 10 cm VAS (range 0–100) and to complete the ESSPRI questionnaire. Four subgroups of fatigue severity were defined, as previously published 1 : no fatigue (VAS=0); low fatigue (VAS=1–24); moderate fatigue (VAS=25–74); high fatigue (VAS=75–100). For each subgroup demographic, serological, histological features and ESSDAI score were collected, as well as the prevalence of pSS-related lymphoma, fibromyalgia (FM), autoimmune thyroiditis, and anaemia. Results: fatigue was reported by the 87.2% (n=75) of pSS patients, distributed in subgroups as following: 25.3% (n=19) with low fatigue, 58.7% (n=44) with moderate fatigue and 16% (n=12) with high fatigue. Lymphoma was significantly (p=0.0133) more frequent in the pSS subgroup with high fatigue (33.4%, by considering active lymphoma cases; 50%, by considering also the cases with lymphoma in remission). FM patients were a minority (4.7% ; n=4), and never complained of high fatigue, all of them reporting moderate fatigue. A significant correlation was finally found between fatigue severity and ESSPRI (p<0.0001), but not with ESSDAI (p=0.31). No significant age or sex difference was observed between subgroups. Also autoimmune thyroiditis, anaemia, anti-SSA and/or anti-SSB positivity, rheumatoid factor positivity, and cryoglobulinemia showed no significant difference between subgroups. Conclusions: when fatigue is better stratified in pSS, it appears that it is usually moderate or severe, rather than mild. Furthermore, it is unrelated to FM. Overall, fatigue appears as a consequence of pSS itself. Of note, severe fatigue was related in this study with the most important complication influencing patient survival in pSS, i.e., lymphoma. Further studies are needed to disclose the pathogenetic events leading to fatigue in pSS, and investigation of lymphoma in pSS might be also helpful to this end. Reference: [1] Ng WF, et al. Transcriptional Signature of Fatigue Derived from Patients with Primary Sjögren's Syndrome. PLoS One2015Dec 22;10(12):e0143970. Disclosure of Interest: None declared